An Evaluation of the Effect of Early Marriage on Girl Child Development in Borno - Saidu, Amina Ramat; Mohammed, Ibrahim; Bare, Mohammed Ibrahim (NIU Journal of Social Sciences; Vol 10 No 3 (2024): NIU Journal of Social Sciences, Vol. 10 No. 3, September 2024DO - 10.58709/niujss.v10i3.2011, 2024)
The study assesses the effect of early marriage on girl child development in Jere L.G.A. Metropolis, Borno State. Related literatures were reviewed based on specific objectives of the study. This study was a survey research method. The target population of the study comprise some selected residence in Maidugiuri, Borno State. The research instrument used for this study was a well-structured questionnaire. The data were analyzed using frequency count and its equivalent percentages score as well as likert scale. The result of the study indicates that many of the respondents strongly agrees that early marriage can make it too difficult for a girl to attend school and perform her duties as wife and mother. Some of the respondents agree with the statement that Education is useful to a girl child even after marriage. While some of them strongly agree to the statement that early marriage increases risk for sexual transmitted diseases (HIV/AIDs). Majority of the respondents strongly agree that early marriage affects girl child in providing health services to their children. It is therefore, recommended that Government should create awareness on the negative effect of early marriage and how it makes girl child education almost impossible. Government should create a policy that will be geared towards discouraging early marriage as death may occur during birth.